Analisis Perbedaan Waktu Transportasi Mukosiliar Hidung Pada Perokok Dan Non Perokok Dengan Uji Sakharin Di Universitas Muslim Indonesia - Permatasari, Dinda; Susilo, Wawan; Wiriansya, Edward Pandu; Abdi, Dian Amelia; Sanna, Andi Tenri (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
The nose has a physiological function for example as a filter that is useful to clean the air of inspiration from dust, bacteria and viruses through a mechanism called the mucociliary transport system (TMS). This TMS mechanism functions to protect the upper and lower respiratory system by forming waves of sweeping on foreign objects such as dust and even microorganisms trapped in the mucous pallets. This study aims to determine whether there are differences in nasal mucociliary transport time in smokers and non-smokers. The material used in this study is sakharin which has a sweetness level 700 times sweeter than ordinary sugar. This study involved 50 research subjects who were divided equally into 2 groups, 25 smokers and 25 non-smokers. All subjects will be interviewed in the form of a questionnaire and then test the time of mucociliary transport of his nose using the sakharin test. The results of this study found that the average mucociliary transport time of the nose to non-smokers was 24.67 ± 5.36 minutes and the mean time of mucociliary transport of the nose to smokers was 9.42 ± 5.04 minutes. Obtained also the results of the average mucociliary transport time of noses in light smokers that is 24.2 ± 5.4 minutes and the average mucociliary transport time of noses in moderate smokers is 27.9 ± 3.94 minutes. It can be concluded that the difference in nasal mucociliary transport time was found in smokers and non-smokers where the mucociliary transport time in smokers was longer.